A two-stage approach for bi-objective integer linear programming - Dai, Rui; Charkhgard, Hadi (Operations research letters, 2018)
We present a new exact approach for solving bi-objective integer linear programs. The new approach employs two of the existing exact algorithms in the literature, including the balanced box and the ϵ-constraint methods, in two stages. A computationally study shows that the new approach has three desirable characteristics. (1) It solves less single-objective integer linear programs. (2) Its solution time is significantly smaller. (3) It is competitive with the two-stage algorithm proposed by Leitner et al. (2016). •We develop a new exact method for bi-objective integer linear programming.•The new method is a two-stage approach.•The new method employs the balanced box method in the first stage.•The new method employs the epsilon constraint method in the second stage.•The new method is faster than both the balanced box and epsilon constraint methods.